Pharmacy Technology: Are You an Enthusiast or a Luddite? - Felkey, Bill G. (Hosp Pharm, 2014)
Technology is here to stay in both our professional and personal lives. Our challenge is to make the appropriate selection and optimize the technologies that we use. This month, we address the pervasiveness of technology, especially in the pharmacy department’s efforts to achieve its mission.